Development of HOTS-based LKPD on student learning outcomes in cell biology material at SMAN 2 Percut Sei Tuan - Rara Soraya; Efrida Pima Sari Tambunan (Master Program of Biology Education, Universitas Lambung Mangkurat, Banjarmasin, Indonesia, 2022)
The Student Worksheet (LKPD) is a learning tool that teachers can use to increase the activities of students in the teaching and learning process. SMA Negeri 2 Percut Sei Tuan is one of the schools that has not used HOTS-based LKPD to improve student learning outcomes. This research produces a HOTS-based LKPD on cell material which aims to determine the feasibility of LKPD products, determine the practicality of LKPD products, and determine student learning outcomes. This study uses a 4D development model by Thiagarajan, Dorothy S. Semmel, and Melvyn I, Semmel with the stages of definition, design, development, and disseminate. The results of material expert validation obtained 93% results, and media expert validation got results of 80% with appropriate criteria so that LKPD was feasible to use. The results of practicality by teachers obtained results of 65.625%, and students got results of 76.16% with practical criteria, so LKPD were practically used as teaching materials. Student learning outcomes got results of 0.72 with very effective criteria, so LKPD is very effectively used to improve student learning outcomes. With the HOTS-based LKPD, teachers can help improve high-level thinking skills so that student learning outcomes are effective.AbstrakLembar Kerja Siswa (LKPD) merupakan salah satu sarana pembelajaran yang dapat digunakan oleh guru dalam meningkatkan aktivitas siswa dalam proses belajar mengajar. SMA Negeri 2 Percut Sei Tuan merupakan salah satu sekolah yang belum menggunakan LKPD berbasis HOTS untuk meningkatkan hasil belajar siswa. Penelitian ini menghasilkan LKPD berbasis HOTS pada materi sel yang bertujuan untuk mengetahui kelayakan produk LKPD, mengetahui kepraktisan produk LKPD, dan mengetahui hasil belajar siswa. Penelitian ini menggunakan model pengembangan 4D oleh Thiagarajan, Dorothy S. Semmel, dan Melvyn I, Semmel dengan tahapan pendefinisian (define), perancangan (design), pengembangan (develop), dan penyebaran (disseminate). Hasil validasi ahli materi memperoleh hasil sebesar 93%, validasi ahli media memperoleh hasil sebesar 80% dengan kriteria sesuai sehingga LKPD layak digunakan. Hasil kepraktisan guru memperoleh hasil 65,625% dan siswa memperoleh hasil 76,16% dengan kriteria praktis sehingga LKPD praktis digunakan sebagai bahan ajar. Hasil belajar siswa diperoleh hasil sebesar 0,72 dengan kriteria sangat efektif sehingga LKPD sangat efektif digunakan untuk meningkatkan hasil belajar siswa. Dengan adanya LKPD berbasis HOTS, guru dapat membantu meningkatkan kemampuan berpikir tingkat tinggi sehingga hasil belajar siswa efektif.